KEKUATAN HUKUM PUTUSAN MAHKAMAH KONSTITUSI SEBAGAI BAHAN PERTIMBANGAN MAJELIS PERMUSYAWARATAN RAKYAT DALAM PEMBERHENTIAN PRESIDEN - Irwansyah & Shela Natasha (Jurisprudensi : Jurnal Ilmu Syariah, Perundangan-Undangan dan Ekonomi Islam, 2018)
The Constitutional Court as the first and the last state administrative court in Indonesia was given the obligation by the 1945 Constitution of the Republic of Indonesia (Constitution) to decide the opinion of the House of Representatives (DPR) regarding alleged violations by the President according to the Constitution. The Constitution has instructed the Constitutional Court to be in the midst of the DPR and the People's Consultative Assembly (MPR) in the mechanism of dismissal of the President, so that the dismissal of the President depends on the MPR decision and does not refer to the decision of the Constitutional Court. The possibility of the MPR to annul the ruling of the Constitutional Court is a gap for experts in constitutional law to debate the legal force of the decision of the Constitutional Court in the mechanism of dismissal of the President. However, it should be understood that the Constitutional Court in terms of dismissal of the President only provides a legal review, so the decision is final and legally binding, where the decision can be a consideration for the MPR in making decisions on the political side. Keywords: Mahkamah Konstitusi, Majelis Permusyawaratan Rakyat, Impeachment Abstrak: Mahkamah Konstitusi sebagai pengadilan administrasi negara pertama dan terakhir di Indonesia diberi kewajiban oleh Undang-Undang Dasar Negara Republik Indonesia (UUD) 1945 untuk memutuskan pendapat Dewan Perwakilan Rakyat mengenai dugaan pelanggaran oleh Presiden menurut Konstitusi. Konstitusi telah memerintahkan Mahkamah Konstitusi untuk berada di tengah-tengah DPR dan Dewan Permusyawaratan Rakyat (MPR) dalam mekanisme pemberhentian Presiden, sehingga pemberhentian Presiden tergantung pada keputusan MPR dan tidak mengacu pada keputusan Mahkamah Konstitusi. Kemungkinan MPR untuk membatalkan putusan Mahkamah Konstitusi adalah celah bagi para ahli hukum konstitusional untuk memperdebatkan kekuatan hukum dari keputusan Mahkamah Konstitusi dalam mekanisme pemberhentian Presiden. Namun, harus dipahami bahwa Mahkamah Konstitusi dalam hal pemberhentian Presiden hanya memberikan tinjauan hukum, sehingga putusannya bersifat final dan mengikat secara hukum, dimana putusan tersebut dapat menjadi pertimbangan bagi MPR dalam mengambil keputusan di sisi politik. Kata kunci: Mahkamah Konstitusi, Majelis Permusyawaratan Rakyat,Impeachment